"Silver Bullet" Milestones in Software History. - Glass, Robert L. (Communications of the ACM, 2005)
Presents the author's comments on the earliest creative milestone in software history. Development of business applications software and an application-specific computer called LEO in 1951; Excitement in the field of computing; Discussion on the history of computing; Reference of computers that were coded in machine language; Ideas in the field of computer software, Emergence of assembly language; Utility of tools called compilers.